IMPLEMENTASI PROGRAM DANCE4LIFE OLEH RUTGERS WORLD POPULATION FOUDATION DALAM MASALAH HIV/AIDS DI KOTA PEKANBARU, RIAU - Popy Safitri Ginting; Faisyal Rani (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2016)
This research explain about Rutgers (World Population Foundation) WPF on HIV/AIDS problem in Pekanbaru, Riau. Rutgers World Population Foundation has a program the program is Dance4life this program discuss about sexual reproduction healthy and HIV/AIDS is one of it. Based on the issue, there is question: “ How is implementation of Dance4life program by Rutgers World Population Foundation on HIV/AIDS problem in Riau society”. Rutgers World Population Foundation asked all authorities to participant and talking action to handle case situation of HIV/AIDS.This research use field research method within direct interview, by e_mail, journals, books and website on key informant as a primer data. This research use perspective constructive, the role of international organizations theory and international Non goverment organization analysis level.This research show that implementation of Dance4life program in Pekanbaru, Riau still do not effective enough it can be seen from the socialisation that is given to the teenagers still can not able to decrease the level of HIV/AIDS in Pekanbaru, Riau. The minim of transportation tools in implementation also one of the cause why this program still can not flow smoothly in Pekanbaru, Riau.Keywords: Rutgers WPF, HIV/AIDS, Dance4life,International Non Government Organization.